Georgia : Technical Assistance Report-Liquidity Management Operations. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report presents an assessment of liquidity management operations in Georgia. The National Bank of Georgia (NBG) has embarked on an ambitious project to strengthen monetary policy implementation so that its actions under normal circumstances are seen by the market as both credible and predictable. Overall, the NBG strategic framework is guided by the need to strike a balance. The NBG is actively implementing its new liquidity coverage ratio as a way of better capturing the liquidity risks of banks. NBG credibility around its monetary policy operations could be further supported through the creation of an operational guideline.